Formulasi Dan Uji Sensori Otak-Otak Cumi Dengan Variasi Penambahan Tepung Eucheuma Spinosum Dan Tepung Tapioka - Triyastuti, Meilya Suzan; Ondang, Hetty Magrittha Paulin; Shitophyta, Lukhi Mulia; Budiarti, Gita Indah; Dewi, Luthfi Kurnia (JURNAL GASTRONOMI INDONESIA, 2024)
"Otak-otak" is a diversification of fishery products that use fishery commodity raw materials. "Otak-otak" made of squid with using tapioca flour and Eucheuma Spinosum seaweed flour. This research aimed to determine the concentration formulation of Eucheuma Spinosum seaweed flour and tapioca flour in "otak-otak". The test analysis in this research is sensory testing and statistical analysis. The results showed that the appearance and texture aspects of Eucheuma Spinosum flour were very popular with the panelists with an appearance value of 8.19 and a texture value of 8.35. Based on the results of statistical tests, significantly different results were obtained (p<0.05) in the aspects of appearance and texture. Therefore, the appearance and texture aspects of using tapioca flour and Eucheuma Spinosum seaweed flour in squid brains in this study affect consumer acceptance because they have a whiter color without slime and have a chewy, compact, and dense texture.